2013
DOI: 10.1684/epd.2013.0602
|View full text |Cite
|
Sign up to set email alerts
|

The clinical outcome of adjuvant therapy with black seed oil on intractable paediatric seizures: a pilot study

Abstract: To evaluate the effect of black seed oil, as add-on treatment to antiepileptic drugs (AEDs), on seizure frequency and severity as well as oxidative stress in intractable epilepsy patients. Methods. A prospective, randomised, single-blinded, controlled, crossover pilot study. Five healthy children were included as controls. Thirty intractable epileptic children were randomly assigned to either Group I or II. Group I received placebo for four weeks, followed by a two-week washout period, and subsequently black s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…A similar clinical trial done by the same author had similar outcomes, although TQ (1 mg/kg) was administered as an add-on therapy instead of water extract of black seed [81]. On the other hand, another study conducted by Shawki et al had a different result; after administration of 40 – 80 mg/kg/day of black seed oil as an adjuvant therapy for 4 weeks, no beneficial effects on the frequency and severity of seizures in intractable epileptic children were observed [82]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar clinical trial done by the same author had similar outcomes, although TQ (1 mg/kg) was administered as an add-on therapy instead of water extract of black seed [81]. On the other hand, another study conducted by Shawki et al had a different result; after administration of 40 – 80 mg/kg/day of black seed oil as an adjuvant therapy for 4 weeks, no beneficial effects on the frequency and severity of seizures in intractable epileptic children were observed [82]. …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some authors have reached results that conflict with the traditional beliefs about NS. Actually, the evidence for the positive effects of NS in the treatment of osteopenic postmenopausal women and intractable epileptic children is conflicting [40, 82, 105]. Therefore, more studies should be planned in these situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the oxidative stress markers were higher in intractable epileptic children compared with healthy children, N. sativa oil supplementation could not improve it, but no side effects were reported during the study (Shawki et al, 2013). However, in another similarly planned study, administration of TQ (the main constituents of the plant) showed antiepileptic effects in children with intractable epilepsy.…”
Section: Effects On Neurological Disordersmentioning
confidence: 87%
“…A double-blind study conducted in epileptic patients treated with Nigella sativa showed a marked reduction in seizure frequency, and it was well tolerated. 36,45 A recent study conducted by George et al (2019) showed that a standardized extract of P. amarus (PHYLLPRO™) containing phyllanthin and hypophyllanthin as an active phytoconstituents ameliorates inflammation and intoxication via inhibition of pro-inflammatory cytokines in hangover populations without serious adverse events. 15 Thus, P. amarus can be considered as a potential herbal therapeutic remedy for the management of epileptic seizures.…”
Section: Discussionmentioning
confidence: 99%